Lexico-semantic peculiarities of a virtual language personality (Eurasian Journal of Philology Science and Education, 2023)
The article is devoted to the study of the current topic of modern linguistics –virtual linguistic personality, aimed at describing the linguistic features of personality and lexico-semantic specifics of virtual linguistic personality in Internet communication.The study began with a review of works on the concept of linguistic personality, studies of domestic and foreign scientists and focused on its features and properties. Given the relevance of studying Internet communication from a linguistic point of view, the existing definitions of the concept of "virtual personality" were analyzed. The article considers a virtual linguistic personality with its special meanings, a changed attitude to time and space, a high degree of involvement in virtual activities, specific goals and communicative strategies, etc. It was considered as a new type of linguistic personality, characterized by lexico-semantic discursiveness.The goal of the – study is to consider the totality of the lexical and semantic properties of a virtual linguistic personality. The object of the study – is a virtual linguistic personality as a participant in a virtual discourse on the Internet. The research method and research materials include comments on the publication "Florida lawmakers strip Disney of special tax status" posted on the BBCNews Instagram page. In the course of the study, the efficiency of the following lexical units was determined in the comments of respondents to the post: slang vocabulary; idioms; colloquial and ordinary language; paremia; occasionalisms; terms and quotations. As a result, a quantitative and comparative analysis of these language units was carried out and conclusions were drawn.Key words: virtual linguistic personality, virtual space, Internet communication, lexico-semantic analysis, comments.